Permasalahan Pemutusan Hubungan Kerja Melalui Artificial Intelligence (AI) - Ivan Mulyono, Ferio; Santoso PN, Sugeng (Faculty of Law, University of Mataram, 2025)
The use of Artificial Intelligence (AI) is already very prevalent and is used in almost all aspects of life. The existence of AI is inevitable. AI makes it very easy in various aspects of life, including in the management of Human Resources. One of the benefits of using AI for Human Resource Management is in assessing worker performance or achievements. AI can also be used in providing important decisions in industrial relations, namely terminating employment. This study discusses regulations related to the use of AI to carry out termination of employment. This research is a normative legal research with a statute approach, a conceptual approach, and a comparative approach. This study concludes that there are different regulations in several countries, Indonesia places AI not as a legal subject, AI regulations in various countries show a paradigm difference that is divided into two, namely prioritizing AI development or protection against the impact of AI and a risk-based approach to ensure strict supervision of the use of AI, especially those that are high risk to workers, such as layoffs carried out by AI.